(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Type 2 Diabetes Mellitus is commonly associated with electrolyte abnormalities due to hyperglycemia, osmotic diuresis, and antidiabetic therapy. Insulin therapy may predispose patients to hypokalemia by promoting intracellular potassium shift. The present study aimed to evaluate electrolyte imbalance, particularly hypokalemia, among Type 2 Diabetes Mellitus patients receiving insulin with oral hypoglycemic agents compared with those receiving oral hypoglycemic agents alone. Methodology: This hospital-based comparative cross-sectional study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from May 2025 to March 2026. A total of 100 patients aged 40–80 years were included, comprising 50 patients receiving insulin with oral hypoglycemic agents and 50 patients receiving only oral hypoglycemic agents. Demographic and clinical details were collected, and serum electrolytes including potassium levels were analyzed using standard laboratory methods. Statistical analysis was performed using SPSS version 26.0. Results: The majority of patients belonged to the 61–70 years age group (35%), with females constituting 54% of the study population. Patients receiving insulin with oral hypoglycemic agents showed a higher prevalence of hypokalemia and lower mean serum potassium levels (3.084±0.358 mEq/L) compared to patients receiving only oral hypoglycemic agents (4.0±0.562 mEq/L). Conclusion: Hypokalemia was more common among Type 2 Diabetes Mellitus patients receiving insulin therapy along with oral hypoglycemic agents. Regular monitoring of serum electrolytes is essential to prevent complications and improve patient outcomes.